The Use of Mind Mapping Technique to Improve The students’ Writing Skill on Analytical Exposition Text In Senior High School - Rini Listyowati; Ina Daril Hanna (Loquen, 2021)
The aim of this study is to use mind mapping to improve students' writing skills on Analytical Exposition Text. Classroom Action Research was used as the method, which consists of two cycles divided into four stages: planning, acting, observing, and reflecting. The instruments used to collect data include a questionnaire, a test, and an observation checklist. The Mind mapping technique was found to be effective in improving the writing skills of SMA AL-MIFTAH Palengaan- Pamekasan students in XI grade Bahasa dan Sastra Inggris on Analytical exposition text. The research found an improvement in the students' writing ability in the second cycle. The students' writing ability scores who achieved the standard achievement/KKM were 26 students, indicating that 87 percent of the students reached the target, and most of the students achieved more than the target of success criteria.